PENGARUH PEMBELAJARAN CONCEPT ATTAINMENT MODEL (CAM) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DI SMA NAHDATUL ULAMA (NU) PALEMBANG - Munir; Dini Afriyansyah; Dewi Sundari (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2017)
This study aims to determine whether the learning model Concept Attainment Model (CAM) affect the Critical Thinking Ability of Students in SMA Nahdatul Ulama (NU) Palembang. This research uses quasi-experimental method (Quasi Eksperimental) with pretest-posttest control group design research design. Sampling is done by saturated sampling technique. The sample of this research is class X IPA 1 and class X IPA 2 in SMA Nahdatul Ulama (NU) Palembang. The results showed that there are differences in critical thinking ability of Animalia subject matter. Improvement Critical thinking ability can be seen on the result before using learning model that is Interpreter indicator, Analysis, Evaluation, Inference (Conclusion), Explanation (Explanation), Self-regulation is 36%, 36%, 37%, 41% 45%, and 46%. Whereas after using Learning Model on interpretation indicator, analysis, evaluation, inference (Conclusion), Explanation (Self Explanation), Self-regulation is 80%, 84%, 85%, 85%, 83%, and 84%. The results showed that this learning model can improve students' critical thinking ability. The results of statistical calculations obtained tcount = 3.474 and ttable of 1.666 with dk (degrees of freedom) of 73 with a significant level of 5% so that tcount> ttable is 3.474> 1.666 and significance value 0.001> 0.05. Based on the hypothesis test, it can be concluded that the influence of learning model Concept Attainment Model to the critical thinking ability of students in SMA Nahdatul Ulama Palembang.